Greater Trochanteric Pain Syndrome (GTPS) - Tordjman, Mickael; Mihoubi, Fadila; Jarraya, Mohamed; Vuillemin, Valerie; Diaz, Luis E.; Roemer, Frank; Guermazi, Ali (Springer Science and Business Media Deutschland GmbH, 2024)
Greater trochanteric pain syndrome (GTPS) is a frequent disorder characterized by lateral hip pain related to different structural causes including gluteus medius and minimus tendinopathy, bursitis, enthesitis, and others and is predominantly seen in middle-aged women. It was referred to in the past as “trochanteric bursitis,” but multiple studies have demonstrated that an isolated bursitis without tendon abnormality is rare. In this chapter, we will describe the anatomy of the greater trochanter and the clinical manifestations and imaging features of the different structural abnormalities associated with GTPS and give an overview of therapeutic options.
CRIS-Team Scopus Importer:2025-02-04